Evaluation of Peri-Implant Bone Repair in Ovariectomized Rats Submitted to the Implant Placement Functionalized with Anti-Sclerostin - Gomes-Ferreira, Pedro Henrique Silva; Frigério, Paula Buzo [UNESP]; Duarte, Nathália Dantas [UNESP]; de Moura, Juliana [UNESP]; Monteiro, Naara Gabriela [UNESP]; da Silva Fabris, André Luis [UNESP]; Okamoto, Roberta [UNESP] (MDPI, 2025)
(1) Background: The challenges in Implantology involve the development of alternative methods to enhance bone repair in patients with systemic conditions, such as osteoporosis. This study aimed to evaluate the effect of a local anti-sclerostin monoclonal antibody (Scl-Ab) on the functionalization of titanium implant surfaces through a dip-coating technique in peri-implant bone repair. (2) Methods: A total of 32 female rats were separated into four groups (n = 8): SHAM NT (Sham surgery), OVX NT (ovariectomy), SHAM Scl-Ab (SHAM; implants functionalized with Scl-Ab), and OVX Scl-Ab (OVX; implants functionalized with Scl-Ab). Implant surgery was executed 30 days after ovariectomy, and the rats were euthanized 28 days postoperatively. The right tibia was used for removal torque and RT-PCR, while the left tibia was collected for micro-CT and laser confocal microscopy. (3) Results: Functionalization with Scl-Ab significantly increased the gene expression of bone markers, especially ALP, in the SHAM Scl-Ab group compared to the other groups (p < 0.05). (4) Conclusions: Some parameters of this study indicate that implants functionalized with anti-sclerostin bone anabolic drug enhance peri-implant bone repair, especially in healthy rats. However, more studies must be carried out to confirm the therapeutic benefits of this approach.